Biomedical porous TiNbZrFe alloys fabricated using NH4HCO3 as pore forming agent through powder metallurgy route. (July 2015) - Li, Y. H.; Yang, C.; Kang, L. M.; Zhao, H. D.; Zhang, W. W.; Li, Y. Y.
<x content-type="archive" xml:space="preserve">Abstract</x> Porous Ti59.38Nb26.6Zr8.7Fe5.32 (wt-%, referred to as TNZF) alloys with high strength and low modulus were successfully fabricated by space holder method through adding ammonium hydrogen carbonate (NH4HCO3). Results show that the fabricated porous TNZF alloys are of β type titanium alloy with adjustable pore characteristics and mechanical properties. Varied amount of NH4HCO3 exerts significant effects on phase constituents, pore characteristics and mechanical properties of the porous alloys. Fracture mechanism of the porous alloys, which is different from the typical brittle fracture as a result of high porosity, exhibits transgranular fracture accompanied with cleavage steps. Strain increased even under low stress during the compressive deformation, demonstrating that the porous alloys possess certain ductility. The porous TNZF alloys with a porosity of 39–53%, an average pore size of 300–800 μm and a compressive modulus of 7–16 GPa and a compressive strength of 117–204 MPa can well meet the requirements of biomedical implant materials.